The Clinic-specific Thesaurus: a Means of “Lean Documentation in Pediatric Surgery - Schaarschmidt, K.; Osada, N.; Kopeke, W. (Methods of Information in Medicine, 1997)
A one-hundred percent documentation rate of diagnoses and patient data is unfeasible and should not be pursued. Therefore, a “lean documentation” of diagnoses and basic patient data was introduced. Coding is done by a clinic-specific list of diagnoses (thesaurus) with a minimum of diagnostic codes, combined with optional free text. By recording the frequency of diagnoses for two years, a thesaurus of 188 diagnostic codes was developed. Bedside coding by treating physicians reduced medical and semantic mistakes of documentation. Cooperation of the clinicians was obtained by shortening the time required for coding to less than two minutes per patient. A documentation assistant supplemented incomplete data in collaboration with the treating surgeons. During a ten-year testing period 93.7% of the hospital-specific codes of our thesaurus were required for documentation, as compared to 13.1% if the same patients were coded by ICD-9. Consequently, coding by a clinic-specific code thesaurus is quick, flexible and accurate.
Keywords: Clinic-specific Thesaurus; Lean documentation; Bedside coding; Documentation Rate; Pediatric Surgery